The mediatory effect of inflammatory markers on the association between a body shape index and body roundness index with cardiometabolic risk factor in overweight and obese women: a cross-sectional study - Mirzababaei, Atieh; Abaj, Faezeh; Khosravinia, Darya; Ghorbani, Moloud; Valisoltani, Neda; Clark, Cain C. T.; Radmehr, Mina; Mirzaei, Khadijeh (Frontiers in Nutrition, 2023)
Abstract Background: Obesity affects body composition and anthropometric measurements. A Body Shape Index (ABSI) and Body Roundness Index (BRI) are reportedly associated with an increased risk of cardiovascular disease. However, the relationship between ABSI, BRI, cardiometabolic factors, and inflammatory elements is not well elucidated. Therefore, this study sought to examine the mediatory effect of inflammatory markers on the association of between ABSI and BRI with cardiometabolic risk factors in overweight and obese women. Methods: This cross-sectional study was performed on 395 obese and overweight women. The typical food intake of individuals was assessed using a 147 items semi-quantitative food frequency questionnaire (FFQ). Body composition was measured by bioelectrical impedance analysis (BIA). Biochemical parameters, such as inflammatory markers and anthropometric components, were also assessed. Result: There was a significant positive association between ABSI with AC and CRI.I in subjects with higher ABSI scores, before and after adjustment (P<0.05). Also, there was a significant positive association between BRI with FBS, TC, TG, AIP, AC, CRI.I, CRI.II, and TyG in participants with higher BRI scores, before and after adjustment (P<0.05). We found that hs-CRP, PAI-1, MCP-1, TGF β and Galectin-3 were mediators of these relationships (P<0.05). Conclusion: Inflammation can play an important role in the relationship between body shape indices and cardiometabolic risk factors among overweight and obese women.